An enhanced authentication with key agreement scheme for satellite communication systems. (14th August 2017) - Qi, Mingping; Chen, Jianhua
Summary: To ensure secure communication in satellite communication systems, recently, Zhang et al presented an authentication with key agreement scheme and claimed that their scheme satisfies various security requirements. However, this paper demonstrates that Zhang et al's scheme is insecure against the stolen‐verifier attack and the denial of service attack. Furthermore, to authenticate a user, Zhang et al's scheme requires large computational load to exhaustively retrieve the user's identity and password from the account database according to a temporary identity and then update the temporary identity in the database. To overcome the weaknesses existing in Zhang et al's scheme, we proposed an enhanced authentication with key agreement scheme for satellite communication systems. The analyses of our proposed scheme show that the proposed scheme possesses perfect security properties and eliminates the weaknesses of Zhang et al's scheme well. Therefore, from the authors' viewpoints, the proposed scheme is more suitable for the authentication scheme of mobile satellite communication systems. Abstract : This work demonstrates the authentication scheme proposed by Zhang et al for satellite communication systems is insecure against to the stolen‐verifier attack, the denial of service attack, and has terrible disadvantages in practice. To overcome these weaknesses, an enhanced authentication scheme without verification table is proposed, which possesses prefect security properties and eliminates the weaknesses of Zhang et al's scheme well. Furthermore, changing password in the improved scheme does not need to interact with the network control center.